Physical parameters optimization of bacterial cellulose from Komagataeibacter sucrofermentans - Muhd Noor, Noor Dina; Oslan, Siti Nurbaya; Mohd Razin, Siti Noorfathiah (Universiti Putra Malaysia, Universiti Pertanian Malaysia Press, 2025)
Many studies have been concerned with nanocellulose's potential to produce environmentally friendly nanomaterial fibers. Bacterial cellulose has shown superiority over plant cellulose, leading to increased research focus on bacterial cellulose production. Among bacterial species, Acetobacter, particularly Komagataeibacter (formerly Gluconacetobacter), has captured interest due to its enhanced bacterial cellulose (BC) production and strain stability. Optimizing production processes becomes imperative with the growing demand for BC in various industries. This study explores the optimization of physical conditions for BC production using Komagataeibacter sucrofermentans. Five parameters—pH, temperature, aeration rate, shaking rate, and surface area, were examined using the One-factor-at-a-time (OFAT) method. This method was selected as it is useful in early-stage optimization to understand the effect of individual factors on BC production. The extracted BC was purified with 4.0 M NaOH solution at 80°C, and wet and dry weights were measured. Analysis via ANOVA determined the significance of each parameter in enhancing BC yield. Optimized conditions from this experiment —pH 5, temperature 20°C, 60% aeration rate, slow agitation (50 rpm), and large surface area fermentation (63.62 cm2) shown to give better BC production. These findings have substantial implications for enhancing BC production efficiency on an industrial scale.